Validation of Improved Dynamic Spectrum and Traffic Management Models of Internet Pricing of Fair DSL-LTE Multiple QoS Network - Fitri Maya Puspita; Syalia Arda; Robinson Sitepu; Yunita; Evi Yuliza; Sisca Oktarina; Sugandi Yahdin (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Currently, the development of communication technology is very rapid, especially on the internet. Therefore, with the increasing need for the internet, the quality of service must also be improved. This study aims to analyze the sensitivity of the internet pricing scheme model using the modified Cloud Radio Access Network (C-RAN) model with the addition of the fair network traffic management variable and combined with the Constant Elasticity of Substitution (CES) utility function. C-RAN is a centralized radio access network to process signals and send them to the core network where the equipment used is connected to cellular antennas. The improved C-RAN model is modified into 2 cases, each of which has 3 pricing schemes, namely flat-fee, usage-based and two-part tariff, with the provision of initial usage and a predetermined amount of bandwidth consumption. This research data is secondary data obtained from the local server of local server traffic data in Palembang. Based on the analysis that has been done, the results of this study indicate that the improved C-RAN model can be utilized by Internet Service Providers (ISPs) to increase profits. The results of the sensitivity analysis for the improved model show that, if the variable is infinity, the increase and decrease are not fixed, whereas if the variable is 0.000 then the increase and decrease are fixed.